2022
DOI: 10.1371/journal.pone.0264024
|View full text |Cite
|
Sign up to set email alerts
|

In silico recognition of a prognostic signature in basal-like breast cancer patients

Abstract: Background Triple-negative breast cancers (TNBCs) display poor prognosis, have a high risk of tumour recurrence, and exhibit high resistance to drug treatments. Based on their gene expression profiles, the majority of TNBCs are classified as basal-like breast cancers. Currently, there are not available widely-accepted prognostic markers to predict outcomes in basal-like subtype, so the selection of new prognostic indicators for this BC phenotype represents an unmet clinical challenge. Results Here, we attemp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…PRAME was classified as a switch gene that significantly correlates with poor overall survival in patients with basal-type breast cancer. These data suggest that PRAME could serve as a prognostic biomarker and/or therapeutic target in TNBC [78].…”
Section: Prame As a Biomarkermentioning
confidence: 73%
See 1 more Smart Citation
“…PRAME was classified as a switch gene that significantly correlates with poor overall survival in patients with basal-type breast cancer. These data suggest that PRAME could serve as a prognostic biomarker and/or therapeutic target in TNBC [78].…”
Section: Prame As a Biomarkermentioning
confidence: 73%
“…This showed that PRAME expression is a prognostic marker for clinical outcomes of breast cancer, independent of traditional clinicopathological markers [77]. Recently, an in silico study on the Cancer Genome Atlas (TCGA) and Breast Invasive Carcinoma (BRCA) dataset led to recognition of a basal-like specific gene signature composed of 11 potential unfavorable prognostic biomarkers, including PRAME [78]. PRAME was classified as a switch gene that significantly correlates with poor overall survival in patients with basal-type breast cancer.…”
Section: Prame As a Biomarkermentioning
confidence: 99%
“…Nowadays, use of gene expression profile to define as prognostic biomarkers of TNBC patients have been still under-investigation. Although other studies found the genes related to poor prognosis, those finding have not applied in clinical practice (10)(11)(12)(13). To develop the new prognostic indicators, more detailed research is required owing to the complex tumor heterogeneity and complicated molecular regulatory mechanism of TNBC.…”
Section: Introductionmentioning
confidence: 99%